Metode Pembelajaran Kreatif dalam Pendidikan Anak Usia Dini - Analisa Gea; Refni Fajar Wati Zega (Institut Nalanda, 2025)
Early childhood education (ECED) plays an important role in shaping children's cognitive, social and emotional development, but conventional learning methods such as lectures and memorization are less effective in stimulating creativity and interest in learning. Therefore, innovations in learning are needed, such as edutainment, project-based learning and educational games, which are proven to increase children's engagement and motivation. In addition, the role of educators in creating an interactive environment and the involvement of parents are also very important. This study uses the literature study method by collecting various references from journals, books and other scientific sources. This literature study shows that innovative methods based on exploration, projects and educational games can improve children's creativity, critical thinking skills and conceptual understanding. Thus, the application of innovative and collaborative learning methods is expected to create a fun learning environment that supports holistic child development.